Auditing Process and Service Delivery In Kabale Local Government, Uganda - David, Kabagambe Jesse; John , Turyasingura; Agaba Moses (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2023)
This study's aim was to ascertain how the auditing procedure affected the provision of services by the Kabale District Local Government. Service delivery was the study's end variable, while the study's predictor variables were how the money was allocated. The cross-sectional survey came before the research. It was decided to conduct both a quantitative and a qualitative analysis using the data from 86 respondents. Frequency tables were employed to explain the data since descriptive analysis required that a single variable and its properties be presented together with the data. A Pearson correlation matrix was used to look at the bivariate correlations between the predictor components and the dependent variable. To fit the data, a linear regression model was employed. According to research results from the regression model, the distribution of money (R=656) has a positive importance on the capability of the local government of Kabale District. The key finding of this study is that service delivery at Kabale District Local Government is impacted by the auditing process, as shown by the findings and discussion. This is consistent with the researcher's subsequent findings. When asked if Integrate is observed in accordance with the auditing process, the respondents' responses revealed that 90.7% of them agreed with the claim and 9.3% were unsure. The study suggests emphasizing the auditing procedure when providing services. Integrate, relationship-building, objectivity, timeliness, and communication should be stressed in order to achieve this.